Arquivo universitário: considerações em torno da questão: panorama da situação no Brasil - Bottino, Mariza (1994)
The present work comprises two main parts. The first one considers the University Archive in the context of University-Archives-Science of Archives. It presents historical background concept, mission, function and objectives as well as other aspects related to its perfomance, exclusivelly based on literature published on the subsject. The second part refers to the development of the subject in Brazil presenting data on institution which pertain to the study group on universities archives, obtained from interviews, questionnaires and visits. Final considerations are done and it is suggested an alert towards thinking the University Archive integrated to the Information System of the University.